Modelos lineales generalizados para la predicción de precipitaciones en el Valle Central de Costa Rica, América Central usando ENOS: una propuesta metodológica - Ramírez Buelvas, Sandra Milena (2015)
The ocean/atmosphere interaction is commonly studied through processes or phenomena such as El Niño / Southern Oscillation (ENSO). Many of the statistical studies on the subject, focus on the use models for continuous time series, adjusting models in the time domain, as in the case of univariate or multivariate ARIMA models. However, not always the primary concern is to determine exactly the magnitude of climatic anomalies such as the amount of rainfall in a period but, categorizing the magnitude of precipitation, to determine the probability of occurrence of class, conditioning on diferent categorizations (i.e. terciles) of ENSO. The objective of this study is to ind and / or develop methodological statistical strategies to estimate these probabilities. In particular, we are interested in assessing and modeling the relationship between the occurrence of El Niño (La Niña) and the variability of precipitation in the Central Region of Costa Rica, in May-June-July season. Data are time series of sea surface temperature (SST) in the area of Niño 3 and the Southern Oscillation Index (SOI) for atmospheric pressure. As the response we used rainfall (R) recorded in Juan Santa Maria airport, Costa Rica. The series were categorized into terciles to build two-way contingency tables. The tables were analyzed using log-linear and proportional odds models, to determine the conditional and joint probabilities of rainfall events. We also estimated a measure of ordinal association.